2019
DOI: 10.1007/s40415-019-00526-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NaCl stress on growth of Portulaca oleracea and underlying mechanisms

Abstract: The purslane Portulaca oleracea L. is a promising crop species for agriculture in saline-alkali soils. Up to date, biochemical and molecular changes in purslane in response to salinity were seldom reported. To investigate biochemical effects of salinity on purslane, seedlings were treated with different concentrations of NaCl for up to 14 days. The results showed that treatments with 150 mM and 200 mM NaCl significantly decreased dry and fresh weight of seedlings, shoot and root length as well as leaflet numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 45 publications
(46 reference statements)
0
5
0
3
Order By: Relevance
“…After 30 days of exposure to 140 mM NaCl, however, there was a clear increase in MDA compared to control. Different results were reported by Xing et al [ 37 ] for treatment with 100, 150, and 200 mM NaCl, which increased MDA- and O 2 -production and resulted in damage to cell membrane integrity and protein activity. They stated that long-term exposure to high salinity might destroy some cell membranes, leading to lower SOD, POD, and CAT activities.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…After 30 days of exposure to 140 mM NaCl, however, there was a clear increase in MDA compared to control. Different results were reported by Xing et al [ 37 ] for treatment with 100, 150, and 200 mM NaCl, which increased MDA- and O 2 -production and resulted in damage to cell membrane integrity and protein activity. They stated that long-term exposure to high salinity might destroy some cell membranes, leading to lower SOD, POD, and CAT activities.…”
Section: Discussionmentioning
confidence: 58%
“…In Arthrocnemum macrostachyum, which is considered to be extremely well adapted to salinity, an increase in net photosynthesis up to a concentration of 510 mM NaCl has been observed [36]. A reduction of the photosynthesis rate and an increase in intercellular CO 2 concentration after 14 days of treatment with 100, 150, and 200 mM NaCl was reported by [37]. Tang et al [38] showed that with increasing NaCl concentration, the intercellular CO 2 concentration of purslane and the values of chlorophyll a/b increased, while the transpiration rate, net photosynthesis rate, stomatal conductivity and chlorophyll content decreased.…”
Section: Discussionmentioning
confidence: 95%
“…Such findings are in total agreement with the previously reported inconclusive differences in MDA level in purslane plants subjected to varying salt stress levels, where the MDA content showed a peak after exposure at 300 mM NaCl for 6 or 9 days [ 57 ]. In general, the increased MDA and O2- synthesis under salt stress has been associated with damage to cell membrane integrity and protein activity, although the damage recorded depends on the stress period [ 58 ]. It has been suggested that long-term exposure to high salinity may lead to the destruction of cell membranes, adversely affecting SOD, POD and CAT activities, whereas oxidative stress-mediated lipid peroxidation does not occur within a short period; e.g., up to 5 week exposure to salt stress [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Portulaca oleracea L. (purslane) (which is a member of Portulacaceae), is a drought-and salt-tolerant annual plant. The plant is a promising crop species in saline-alkali soils [16,17]. Moreover, P. oleracea could effectively absorb salts from soil media to remediate saline-alkali soils [18].…”
Section: Introductionmentioning
confidence: 99%